HPLC for at-line reaction monitoring and purification improves yield and purity of tRNA - Megušar, Polona; Calder, Ewen D. D.; Vodopivec Seravalli, Tina; Lebar, Sergeja; Walport, Louise J.; Sekirnik, Rok (Frontiers in Molecular Biosciences, 2024)
Engineered transfer RNA is an emerging therapeutic modality, particularly suited to treatment of diseases caused by genetic disorders based on premature termination codons, frameshifts, or missense mutations. It is also extensively used in reprogramming of in vitro translation systems to generate non-canonical amino acid-containing proteins and peptides, such as in mRNA display. Due to its length, chemical synthesis of tRNA is challenging and production of engineered tRNA at scale is currently limited to in vitro transcription from a DNA template. Previously, the highest reported in vitro transcription yield was 2.5 g/L, significantly below the industry standard for mRNA production of 7–10 g/L. To improve this process, we implemented monitoring of nucleoside triphosphate consumption and tRNA production during in vitro transcription, using at-line high-performance liquid chromatography, with a monolithic solid phase. This allowed for optimization of nucleoside triphosphate concentration, reduction of the in vitro transcription time to <4 h, and improvement of yield up to 4.7 g/L. A step-elution purification on a DEAE chromatographic monolith with >90% step yield was then developed. These improvements in the production and purification of tRNA represent an important step in facilitating production of tRNA for research purposes, and provide a method for purification of therapeutic tRNAs that is scalable and compatible with Good Manufacturing Practice requirements for clinical production